2012
DOI: 10.1186/1746-6148-8-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of ELISAs for monitoring exposure of pig herds to Brachyspira hyodysenteriae

Abstract: BackgroundSwine dysentery (SD), a mucohaemorrhagic diarrhoeal disease of pigs, results from infection of the large intestine with the spirochaete Brachyspira hyodysenteriae. ELISA systems using whole spirochaete cells (WC) and the B. hyodysenteriae outer membrane lipoprotein Bhlp29.7 previously have been established as potential diagnostic tools for SD. However, their true value in identifying infected herds remains unclear. The present study aimed to compare the performance of whole-cell and Bhlp29.7 based EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
7
0
1
Order By: Relevance
“…55,81 Enzyme-linked immunosorbent assay (ELISA)-based techniques for the detection of antibodies to lipopolysaccharide antigen are effective in differentiating B. hyodysenteriae infection from B. innocens ; however, these assays are serotype specific and therefore not universally applicable. 64 Recently, novel serologic assays have been developed with improved specificity to detect circulating antibodies against B. hyodysenteriae- specific outer membrane lipoproteins and may be useful for detecting infected pigs 75,114 ; however, these assays have not yet found broad application. Recent work has also suggested that ELISAs run on meat juices at slaughter may be useful in detecting herds infected with B. hyodysenteriae .…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…55,81 Enzyme-linked immunosorbent assay (ELISA)-based techniques for the detection of antibodies to lipopolysaccharide antigen are effective in differentiating B. hyodysenteriae infection from B. innocens ; however, these assays are serotype specific and therefore not universally applicable. 64 Recently, novel serologic assays have been developed with improved specificity to detect circulating antibodies against B. hyodysenteriae- specific outer membrane lipoproteins and may be useful for detecting infected pigs 75,114 ; however, these assays have not yet found broad application. Recent work has also suggested that ELISAs run on meat juices at slaughter may be useful in detecting herds infected with B. hyodysenteriae .…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Swine dysentery (SD) is endemic in many regions of the world. The disease typically presents 44 as a severe mucohaemorrhagic colitis mainly in grower and finisher pigs, although clinical 45 signs may be ameliorated or prevented by the use of antimicrobial agents (Hampson 2012). 46…”
Section: Introduction 43mentioning
confidence: 99%
“…Enzyme-linked immunosorbent assays (ELISAs) have the potential to be used as rapid, sensitive and reproducible procedures for quantifying serum antibodies to B. hyodysenteriae, and providing indirect evidence of the current or past disease status of an individual pig, and/or of the herd of origin. ELISAs using sonicated whole cells or lipooligosaccharide (LOS) from B. hyodysenteriae as plate-coating antigens have been reported to be sensitive enough to allow detection of SD at a herd level, if sufficient pigs are tested (Joens et al, 1982;Wright et al, 1989;Smith et al, 1991;Song et al, 2012). Unfortunately, false-positive reactions hampered further development of these assays (La and Hampson, 2001).…”
Section: Introductionmentioning
confidence: 99%